2019
DOI: 10.17065/huniibf.454560
|View full text |Cite
|
Sign up to set email alerts
|

Uluslararasi Gi̇ri̇şi̇mci̇li̇k Yöneli̇mi̇ni̇n Yeni̇li̇kçi̇li̇k Boyutu: Küresel Doğan İşletmeler Üzeri̇ne Ni̇tel Bi̇r Çalişma

Abstract: 1990'lı yıllardan itibaren uluslararasılaşma süreci modeli ile faaliyetlerini diğer ülke pazarlarına götürmekte olan işletmelerden farklı, daha erken ve hızlı bir şekilde uluslararasılaşan işletmelerin varlığı belirlenmeye başlanmıştır.  Kuruldukları andan itibaren veya kuruluşlarını takiben kısa bir süre içerisinde uluslararası faaliyetlerde bulunan küçük ve orta ölçekli işletmeler “Küresel Doğan İşletmeler” olarak isimlendirilmektedir. Küresel doğan işletmelerin uluslararasılaşma süreci modeli ile uluslarara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Similarly, Yalçın and Üner (2019) examined the innovation dimension of international entrepreneurship within born global firms. Analyzing firms across sectors in Ankara, Çorum, and Konya, the study identified four factors influencing the innovation dimension: information creation and sharing, entrepreneurship, information and communication technologies, and human resources.…”
Section: Research In the Scope Of Türkiyementioning
confidence: 99%
“…Similarly, Yalçın and Üner (2019) examined the innovation dimension of international entrepreneurship within born global firms. Analyzing firms across sectors in Ankara, Çorum, and Konya, the study identified four factors influencing the innovation dimension: information creation and sharing, entrepreneurship, information and communication technologies, and human resources.…”
Section: Research In the Scope Of Türkiyementioning
confidence: 99%